2022
DOI: 10.1021/acs.inorgchem.2c00448
|View full text |Cite
|
Sign up to set email alerts
|

Catalysis of the Water Oxidation Reaction in the Presence of Iron and a Copper Foil

Abstract: The oxygen evolution reaction (OER) can provide electrons for reducing water, carbon dioxide, and ammonia. On the other hand, copper compounds are among the most interesting OER catalysts. In this study, water oxidation of a Cu foil in the presence of K2FeO4, a soluble Fe source, under alkaline conditions (pH ≈ 13) is investigated using electrochemical methods, X-ray diffraction, X-ray photoelectron spectroscopy, in situ visible spectroelectrochemistry, Raman spectroscopy, and scanning electron microscopy. Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…The oxidation peak for the anodized electrode overlapped with the OER area. Based on previously published results, , these shifts correspond to increased Fe content in the anodized foam (Figure S1). Comparing Ni peaks for the fresh and anodizing foams shows that the amount of active material based on the Ni redox is significantly higher in the anodized electrode.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…The oxidation peak for the anodized electrode overlapped with the OER area. Based on previously published results, , these shifts correspond to increased Fe content in the anodized foam (Figure S1). Comparing Ni peaks for the fresh and anodizing foams shows that the amount of active material based on the Ni redox is significantly higher in the anodized electrode.…”
Section: Resultssupporting
confidence: 75%
“…Oxidation of nickel and its related redox features have been widely investigated. The effect of anodization on the OER was investigated using chronoamperometry (CA) and cyclic voltammetry (CV), and the potential of 60 V was selected as the optimized potential to prepare the anodized electrode (Figure ). Anodization at higher potentials is not possible in our setup due to the potential electrical spark between the two electrodes and the increase in the temperature of the electrolyte.…”
Section: Resultsmentioning
confidence: 99%
“…This increase in the Ni/Fe ratio occurs because of the anodization process at high potential, which removes Fe ions. Other groups also reported that Fe removal on the electrode surface occurs during the OER. …”
Section: Resultsmentioning
confidence: 99%
“…Indeed, such changes in peaks are observed where Fe is removed from Fe/Ni (hydr)­oxide. Especially at high anodization potentials, the oxidation of Fe to FeO 4 2– could result in Fe depletion on the surface of the electrode (Figure c). On the other hand, after the anodization at 30–50 V, a new peak is observed at 1.30–1.35 V, which is related to Ni (hydr)­oxide with small Fe content. Such shifts in peaks are observed where Fe is removed from Fe/Ni (hydr)­oxide.…”
Section: Resultsmentioning
confidence: 99%